2019
DOI: 10.1021/acs.jpcc.9b00862
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stoichiometry on the Mechanism and Kinetics of Oxidative Dissolution of UO2 Induced by H2O2 and γ-Irradiation

Abstract: Radiation-induced oxidative dissolution of uranium dioxide (UO2) is one of the most important chemical processes of U driven by redox reactions. We have examined the effect of UO2 stoichiometry on the oxidative dissolution of UO2 in aqueous sodium bicarbonate solution induced by hydrogen peroxide (H2O2) and γ-ray irradiation. By comparing the reaction kinetics of H2O2 between stoichiometric UO2.0 and hyper-stoichiometric UO2.3, we observed a significant difference in reaction speed and U dissolution kinetics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
(75 reference statements)
0
20
0
Order By: Relevance
“…This is in line with the change in kinetics observed in the powder experiments discussed above. 18,22 Since the dissolution yields are considerably higher for powders, a change in the redox reactivity also has a significant impact on the overall reactivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with the change in kinetics observed in the powder experiments discussed above. 18,22 Since the dissolution yields are considerably higher for powders, a change in the redox reactivity also has a significant impact on the overall reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we have studied the oxidative dissolution of UO 2 pellets at H 2 O 2 exposures ranging from 0.33 mol m −2 to 1.36 mol m −2 . Based on the experimental results of this and previous studies, 18,20,22 the effect of H 2 O 2 exposure on the UO 2 surface reactivity is analysed and discussed.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…They varied from hot-cell studies on leaching of real spent nuclear fuel [2][3][4] to lab experiments using UO 2 -powder, 5 UO 2 -pellets doped with non-radioactive isotopes of fission products [6][7][8] or alpha-emitters 9 suspended in aqueous solutions with or without H 2 O 2 5 or exposed to external gamma-fields in aqueous systems. [10][11][12][13] Due to the complexity of even the simplest of the model systems, many mechanistic aspects have only been indirectly confirmed from experiments. The reaction between the molecular radiolysis product H 2 O 2 and UO 2 is one example.…”
Section: Introductionmentioning
confidence: 99%
“…5 Initially, the oxidants will dominate the surface reactions for kinetic reasons. 6 Assessment of the relative impact of radiolytic oxidants under repository conditions revealed that H 2 O 2 is the oxidant of main importance. 7 In addition to oxidizing UO 2 , H 2 O 2 can also undergo catalytic decomposition on the UO 2 surface.…”
Section: Introductionmentioning
confidence: 99%